Cover Feature: Lipid Internal Dynamics Probed in Nanodiscs (ChemPhysChem 19/2017). Issue 19 (22nd September 2017) - Martinez, Denis; Decossas, Marion; Kowal, Julia; Frey, Lukas; Stahlberg, Henning; Dufourc, Erick J.; Riek, Roland; Habenstein, Birgit; Bibow, Stefan; Loquet, Antoine
Abstract : The Back Cover picture illustrates the intriguing thermotropism of lipids in nanodiscs above and below the phase transition. Solid‐state NMR reveals that the restricted area in nanodiscs decreases the cooperativity of lipid phase transition, maintaining fluidity below the phase transition. However, at room temperature, lipid diffusion is less pronounced in the nanodisc belt compared to liposomes. More information can be found in the Full Paper by S. Bibow, A. Loquet, and co‐workers on page 2651 in Issue 19, 2017 (DOI:10.1002/cphc.201700450 ).